(untitled) (Tanzania Medical Journal, 2021)
Background Health insurance is one of the health financing methods aiming at bringing equity in health care by providing access of quality and affordable health care services to all groups of the population. In Tanzania, children are mainly covered as dependents with no well- established insurance programmes that target children. The burden of out of pocket payments for health care and hence low health care utilization for the uninsured is significant. Study Objective To assess the role of health insurance on health service utilization among children in Misungwi District. Methods A multi-stage cluster sampling was used and interview administered questionnaire with both closed and open ended questions was used to gather primary data on insurance coverage patterns, health care utilization and facility pretences in Misungwi. The sample size used was 227. Analysis was done using statistic computer software SPSS version 20 and data was interpreted and presented based on objectives. Results Health Insurance coverage among children was found to be low with overall coverage being 16.7%. Health insurance status of the child was found to influence health care seeking behaviour of parents and hence health care utilization of the child. Out of pocket payments burden to parents of the uninsured children was evident with 13.6% reporting to borrow money from relatives. Conclusion In this study, it was found that health insurance coverage is low and the child’s health insurance coverage influence the health care seeking behaviour with high cost burden to uninsured children. The need for health insurance coverage is importance for improvement of health service utilization and thus worth further studies.